Hak Asasi Manusia dalam Pandangan Ibnu ‘Asyur: Analisis Q.S al-Maidah: 32 Tafsir al-Tahrir wa al-Tanwir - Eko Saputra; Ahmad Fathoni; Mushliati (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
This research is motivated by the rampant news of recent murder cases on various social media pages, hence this study aims to analyze the phenomenon of human rights in the contemporary era using Ibn 'Asyur's perspective which is considered to have a positive cultural impact for social benefit to the community, especially in the book of tafsir al-Tahrir wa al-Tanwir in Q.S al-Maidah verse 32. This research uses a qualitative method of literature study type with content analysis on the interpretation of Q.S al-Maidah verse 32 perspective of Ibn 'Asyur and other relevant sources. The results showed that in responding to the phenomenon that violates human rights on a large scale (murder), the people who are the object should use the way not to kill each other. However, using one of the stages of mediation in order to get the best solution, by not eliminating the lives of others.